Rediscovery of Pristepyris Kieffer (Hymenoptera, Bethylidae), a new synonym of Acrepyris Kieffer - Azevedo, Celso O.; Alencar, Isabel D. C. C. (Zootaxa, 2009)
The Epyrinae genus Pristepyris Kieffer is revised. The genus has four species. Pristepyris rugicollis Kieffer from Malaysia and P. levicollis Kieffer from Madagascar are rediscovered. Their adult male holotypes are redescribed and illustrated. Specimens of Pristepyris agraensis Kurian and P. flavicornis Kieffer were unavailable and reassigned based on their original descriptions. All species are considered to be Pristocerinae, because they have the metanotum well developed medially. Pristepyris rugicollis is transferred to Acrepyris Westwood because it has the aedeagus divided in three valvae, P. agraensis is transferred to Acrepyris, because it has an undivided hypopygium; and P. levicollis and P. flavicornis are transferred to Pristocera Klug, because they have a hypopygium that is deeply divided into two lobes. Pristepyris is considered junior synonym of Acrepyris, because Pristepyris rugicollis is its type-species.